2016
DOI: 10.3174/ajnr.a4756
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Ultrasonography in Infantile Encephalitic Beriberi: A Useful First-Line Imaging Tool for Screening and Diagnosis in Suspected Cases

Abstract: BACKGROUND AND PURPOSE:Brain imaging is central to the diagnosis of infantile encephalitic beriberi. Because cranial sonography findings have not been described in infantile encephalitic beriberi, our aim was to investigate its role in the diagnosis of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Some children with beriberi and adults with Wernicke's encephalopathy display similar brain changes on magnetic resonance imaging, specifically, bilateral, symmetric hyperintensity signals in the mammillary bodies, thalamic, and periaqueductal areas; however, pediatric brain neuroimaging may also show lesions in the basal ganglia and the frontal lobes. In a recent study of infants with thiamine deficiency encephalopathies, cranial ultrasound revealed hyperechoic lesions of the basal ganglia …”
Section: Thiamine Deficiency and Its Consequencesmentioning
confidence: 98%
See 2 more Smart Citations
“…Some children with beriberi and adults with Wernicke's encephalopathy display similar brain changes on magnetic resonance imaging, specifically, bilateral, symmetric hyperintensity signals in the mammillary bodies, thalamic, and periaqueductal areas; however, pediatric brain neuroimaging may also show lesions in the basal ganglia and the frontal lobes. In a recent study of infants with thiamine deficiency encephalopathies, cranial ultrasound revealed hyperechoic lesions of the basal ganglia …”
Section: Thiamine Deficiency and Its Consequencesmentioning
confidence: 98%
“…Beriberi in older infants and children may present with predominant neurological symptoms, including loss of appetite, nystagmus, ophthalmoplegia, bulging fontanelle, and loss of consciousness . In areas with low awareness of thiamine deficiency, symptoms are easily mistaken for meningitis.…”
Section: Thiamine Deficiency and Its Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The echocardiogram will be completed at baseline (ie, prior to or soon after the first thiamine administration) and repeated at 24 and 48 hours. Since normalisation of encephalitic beriberi occurs slowly,12 the cranial ultrasound will be performed once during the hospital stay, typically within the first 12 hours.…”
Section: Methods and Analysismentioning
confidence: 99%
“…During later infancy, the cry may sound hoarse or change to a soundless cry (4–6 months of age) and neurological symptoms may present, including nystagmus, convulsions and unconsciousness (7–9 months of age). Infants with encephalitic beriberi were found to have abnormal cranial ultrasonography, with normalisation within 8 weeks of thiamine administration 12. In the second year of life and later in childhood, TDD more typically presents with a broad range of neurological symptoms, such as anorexia, irritability, agitation, muscle pain, reduced deep tendon reflexes, ataxia, paralysis and altered levels of consciousness 11 13–15.…”
Section: Introductionmentioning
confidence: 99%